Bridging UX and web development : better results through team integration - Moffett, Jack (Jack Lean) (Morgan Kaufmann, 2014)
This book prepares the reader to break down the walls of UX and Web development by teaching how to integrate with the team's developers. It examines the process from their perspective, discovering tools and coding principles that will help bridge the gap between design and implementation. With these tried and true approaches, the reader will be able to capitalize on a more productive work environment. Coverage includes: establishing a collaboration lifecycle by mapping design activities to counterparts in the software development process; software tools that will improve productivity and collaboration; step-by-step exercises that teach front-end coding principles to improve prototyping and implementation activities; practical, usable HTML and CSS examples; and tips for working with various developer personas. --